Submission of the use of the method of preemtive analgesia with acetaminophen for perioperative period in children - Dmytriiev, D V; Marchuk, O V; Vitkovskyi, V L; Kebenko, V Yu (Pain medicine, 2019)
In the structure of postoperative anesthesia in children, as well as in other age groups, the main place is occupied by narcotic analgesics; the route of administration is traditional– intramuscular. The purpose of the study was to in-crease the effectiveness of postoperative analgesia with opioid analgesics in children. The study was conducted in 37 children with a mean age of 3.2 ± 0.8 years operated on tumors in the peritoneal space (27 children, 73%), kidney tumors (8chil-dren, 22%) and ovarian tumors (2 children, 5%). Comprehensive study of the reactions of pain behavior, physiological parameters and laboratory stress tests showed that the use of the scheme of analgesia based on acetaminophen 30 mg/kg and the method of continuous infusion of drugs (fentanyl in a dose of 5 μg/kg/h) for postoperative anesthesia leads to effective analgesia after traumatic operations in the neonatal period. The use of the method of continuous intravenous infusion of opioid analgesics leads to a pronounced, to varying degrees, sedation and respiratory depression, which enables children to adapt well to the apparatus of mechanical ventilation after various surgical interventions.